Dried Skeletonema costatum in Feed Formulation for the Growth of Vaname Shrimp (Litopenaeus vannamei) - Lestari, Dewi Putri; Ekawati, Arning W.; Maftuch, Maftuch (Graduate School, Universitas Brawijaya, 2014)
The aim of this study was to determine the effect and the best dosage used by the Skeletonema costatum in feed formulation on the growth of Vaname shrimp. This experiment used Completely Randomized Design (CRD) with four treatments and three replications. Treatment was given by using dried S. costatum in feed formula (iso protein 37% and iso energy 3.6 kkal/g feed). Feed treatment was the substitution of fish meal protein A = 0%, B = 2.5%, C = 5% and D = 7.5% with dried S. costatum protein. The observed parameters include Survival Rate (SR), Survival Growth Rate (SGR), Feed Efficiency Ratio (FER), and Protein Efficiency Ratio (PER). The results showed that the use of dried S. costatum in feeding are effective in increasing the specific growth rate, feed efficiency ratio and the ratio of protein efficiency than controls. The best dosage in feeding formula is ranged from 4.39% to 4.75%.Keywords: feeding formula, Skeletonema costatum, Vaname Shrimp